Interaction between Lactobacillus reuteri and periodontopathogenic bacteria using in vitro and in vivo (G. mellonella) approaches - Santos, Thaís Aguiar; Scorzoni, Liliana; Correia, Raquel; Junqueira, Juliana Campos; Anbinder, Ana Lia (Oxford Academic, 2020)
Periodontitis is a multifactorial inflammatory disease, and the major cause of tooth loss in adults. New therapies have been proposed for its treatment, including the use of probiotics such as Lactobacillus reuteri. The objective of this study was to evaluate the antimicrobial effects of L. reuteri: live, heat-killed and culture filtrate (cell-free supernatant), on periodontopathogenic bacteria (Fusobacterium nucleatum and Aggregatibacter actinomycetemcomitans) in vitro, as well as the in vivo survival curve, hemocyte density and microbial recovery using Galleria mellonella. For in vitro assays, all preparations reduced colony forming units of F. nucleatum, while only live L. reuteri reduced the growth of A. actinomycetemcomitans. All treatments reduced periodontopathogenic bacteria growth in vivo. The treatment with the supernatant increased the survival of larvae infected with F. nucleatum more than the treatment with live L. reuteri, and none of the treatments altered the survival of A. actinomycetemcomitans-infected larvae. In addition, the treatment with L. reuteri preparations did not alter the hemocyte count of F. nucleatum- and A. actinomycetemcomitans-infected larvae. This study demonstrated that L. reuteri preparations exerted antimicrobial effects and increased the survival of G. mellonella infected by F. nucleatum, although only live L. reuteri was able to reduce the growth of A. actinomycetemcomitans in vitro.
Keywords: Periodontal diseases; Probiotics; Fusobacterium nucleatum; Aggregatibacter actinomycetemcomitans; Lactobacillus reuteri; Galleria mellonella